2022
DOI: 10.3390/antiox11030490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hemp Seed Oils Stability under Accelerated Storage Test

Abstract: The interest in hemp seed oil has recently increased, due to the latest regulations which allow its use as food. Hemp seed oil is characterized by a high content of polyunsaturated fatty acids, which are highly prone to oxidation. Accelerated thermal oxidation (60 °C, 18 days) has been applied to nine types of cold-pressed hemp seed oils to monitor the evolution of the samples during oxidative deterioration. The results showed that the only determinations of primary (peroxide value) and secondary (TBARs) oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 54 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…The presence of a unique acid was detected, i.e., stearidonic acid (C18: 4, SDA), in the range of 1.23 to 1.58%, which makes this oil nutritionally more valuable. A comparatively lower presence of stearidonic acid (1.2%) was previously reported by other researchers [18]. SDA acts as a biological precursor for longer-chain n−3 fatty acids, which can be rapidly synthesized in the human body, i.e., eicosapentaenoic acid (EPA; C20: 5 n−3) and docosahexaenoic acids (DHA; C22: 6 n−3) [19].…”
Section: Fatty Acid Compositionmentioning
confidence: 73%
“…The presence of a unique acid was detected, i.e., stearidonic acid (C18: 4, SDA), in the range of 1.23 to 1.58%, which makes this oil nutritionally more valuable. A comparatively lower presence of stearidonic acid (1.2%) was previously reported by other researchers [18]. SDA acts as a biological precursor for longer-chain n−3 fatty acids, which can be rapidly synthesized in the human body, i.e., eicosapentaenoic acid (EPA; C20: 5 n−3) and docosahexaenoic acids (DHA; C22: 6 n−3) [19].…”
Section: Fatty Acid Compositionmentioning
confidence: 73%
“…Several investigations have sought to increase cannabinoid content using JA or methyl-JA treatments on Cannabis flowers [ 154 ], leaves [ 155 ], or cell cultures [ 156 ] and have been met with mixed results. Studies that analyze oxylipin levels in Cannabis tissues or products have focused on volatiles from above-ground tissues [ 157 ], seeds [ 158 ], or seed oil [ 159 , 160 ] as components of their odor profiles. Recently, it was found that sex impacts the distinct oxylipin species that accumulate in the Cannabis flower.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these, mainly chlorophylls in hemp oil, are undesirable pigments as they lower the oil quality by affecting color, flavor, clarity, nutritional value and oxidative stability. Indeed, the stability of vegetable oils depends on various influences, but mainly on their fatty acid composition, the amount of natural antioxidants, the presence of oxygen and different storage conditions (Liang et al, 2015(Liang et al, , 2018Mahoney et al, 2018;Tura et al, 2022). Chlorophylls, fat-soluble pigments present in many raw vegetable oils, especially in hempseed oils, are undesirable compounds, because they are retained in the oil during cold pressing, making it dark and giving it an unpleasant taste, and acting as a pro-oxidant in oils exposed to light.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the chlorophyll content in linseed oil is low if compared with other seed oils, although a certain variability linked to specific varieties was found, highlighted by a different oil color (Mahoney et al, 2018;Suri et al, 2020). On the other hand, several studies have shown that linseed oil is rich in some compounds, such as tocopherol and carotenoids which exhibit strong antioxidant properties, protecting the oil from oxidation as well as providing health benefits to humans (Liang et al, 2015;Tura et al, 2022). At farm level, in order to ensure a quality product from a short supply chain, the main aim is to maintain desirable antioxidant components, while removing unwanted impurities as much as possible, minimizing the oil loss (Chew et al, 2017(Chew et al, , 2019Tura et al, 2022).…”
Section: Introductionmentioning
confidence: 99%